The enigma girl - Porter, Henry, 1953- (Atlantic Monthly Press, 2025)
"From internationally bestselling author who is "filling the gap left by Len Deighton and John le Carré" (Evening Standard ) comes a propulsive espionage thriller for fans of Mick Herron, Daniel Silva, and Olen Steinhauer. Meet disgraced M15 agent Slim Parsons, a character who-like Lisbeth Salander-will sear your soul. Slim Parsons is all but burned. When her last deep-cover job for M15 ended with a life-and-death struggle on a private jet, she went on the run from her deadly target-a conniving businessman and money launderer codenamed "Hagfish." Now she's back at home, in hiding from her angry bosses in the Security Service, who have accused her of being overly violent and unsuitable for the role of an M15 operative. But after several months off the grid, Slim is called back to another job-Operation Linesman-where she is asked to infiltrate a news website Middle Kingdom whose explosive articles clearly show that they've hacked into the most high-security government databases. She accepts the assignment on condition that the Security Service searches for her missing brother. But Linesman turns out to be anything but simple. Slim uncovers a curious connection between the Middle Kingdom hackers and the legendary Bletchley Park codebreakers. Her new colleagues are becoming suspicious of her intentions, and Hagfish is out for revenge and threatening M15 itself as it all comes together in a shocking crescendo. And all the while she is being watched by someone even deeper in the shadows than she is"--